2017
DOI: 10.1257/pol.20150029
|View full text |Cite
|
Sign up to set email alerts
|

Dishonesty and Selection into Public Service: Evidence from India

Abstract: Students in India who cheat on a simple laboratory task are more likely to prefer public sector jobs. This paper shows that cheating on this task predicts corrupt behavior by civil servants, implying that it is a meaningful predictor of future corruption. Students who demonstrate pro-social preferences are less likely to prefer government jobs, while outcomes on an explicit game and attitudinal measures to measure corruption do not systematically predict job preferences. A screening process that chooses high-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
140
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(157 citation statements)
references
References 43 publications
7
140
1
1
Order By: Relevance
“…Theoretical argumentation and empirical evidence suggest that this seems not to be the case. Several recent studies showing that behavior in lying experiments significantly correlates with cheating behavior outside the lab (Cohn & Marechal, 2018;Dai, Galeotti, & Villeval, 2017;Hanna & Wang, 2017;Potters & Stoop, 2016); see Abeler et al (forthcoming) for a comprehensive overview. From an empirical point of view, audits alone (without a fine) do not seem to significantly affect health care providers' behavior (Lindeboom et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical argumentation and empirical evidence suggest that this seems not to be the case. Several recent studies showing that behavior in lying experiments significantly correlates with cheating behavior outside the lab (Cohn & Marechal, 2018;Dai, Galeotti, & Villeval, 2017;Hanna & Wang, 2017;Potters & Stoop, 2016); see Abeler et al (forthcoming) for a comprehensive overview. From an empirical point of view, audits alone (without a fine) do not seem to significantly affect health care providers' behavior (Lindeboom et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, those subjects who engaged in behavior considered severely dishonest in college also engaged in behavior considered severely dishonest at work. Several recent studies showing that behavior in lying experiments significantly correlates with cheating behavior outside the lab (Cohn & Marechal, 2018;Dai, Galeotti, & Villeval, 2017;Hanna & Wang, 2017;Potters & Stoop, 2016); see Abeler et al (forthcoming) for a comprehensive overview. 15 In Germany, hospitals are audited by the MDK of the SHI.…”
Section: Discussionmentioning
confidence: 99%
“…While no individual report can be identified as truthful or not (and subjects should thus report the payoff‐maximizing outcome under the standard economic assumption), the researcher can judge the reports of a group of subjects. This paradigm is the one used most widely in the literature and several recent studies have shown that behavior in it correlates well with cheating behavior outside the lab (Hanna and Wang (), Cohn and Maréchal (), Cohn, Maréchal, and Noll (), Gächter and Schulz (), Potters and Stoop (), Dai, Galeotti, and Villeval ())…”
Section: Introductionmentioning
confidence: 99%
“…Since a large fraction of public goods in developing countries are provided locally, improvements in the quality of local governance have a large potential to improve the well-being of the poor. In this aspect, this paper also relates to the nascent literature on the determinants of public sector effectiveness in developing countries (Dal Bó, Finan, and Rossi 2013;Hanna and Wang 2016;Callen et al 2014;Ashraf, Bandiera, and Lee 2015;Rasul and Rogger forthcoming).…”
mentioning
confidence: 96%